Complete Response of Hereditary Leiomyomatosis and Renal Cell Cancer (HLRCC)-Associated Renal Cell Carcinoma to Pembrolizumab Immunotherapy: A Case Report - Wang, Tao; Huang, Yan; Huang, Xing; Lv, Zheng; Tian, Shuo; Ma, Xin; Zhang, Xu (Frontiers in Oncology, 2021)
Hereditary leiomyomatosis and renal cell cancer (HLRCC) is a rare autosomal dominant disorder that results from a germline mutation in the fumarate hydratase gene (FH); it manifests as cutaneous leiomyomas, uterine fibroids, and renal cell cancer (RCC). Patients with HLRCC-associated RCC (HLRCC-RCC) have aggressive clinical courses, but there is no standardized therapy for advanced HLRCC-RCC. Here, we describe aggressive HLRCC in a 26-year-old man who presented with RCC that exhibited a novel heterozygous germline insertion mutation in exon 2 of the FH gene (c.191dupA: p.N64fs). Systemic lymph node metastasis had already occurred. The patient underwent robot-assisted laparoscopic resection of the right kidney, but new metastases appeared within 5 months postoperatively. Histological staining of the resected tumor showed high expression levels of programmed cell death-ligand 1 (PD-L1) and programmed cell death-1 (PD-1). The patient was treated with anti-PD1 antibody as first-line therapy. After 2 years of immune checkpoint inhibitor (ICI) treatment, all lesions had disappeared; this response was maintained at 51 months. To our knowledge, this is the first successful treatment of HLRCC-RCC with single-agent immunotherapy. Our approach might be effective for patients with advanced HLRCC-RCC.